Pola Komunikasi Dakwah Ar-Risalah dalam Pembinaan Masyarakat Muallaf Suku Akit di Desa Sungai Upih Kecamatan Kuala Kampar Kabupaten Pelalawan - Ranti Santriyani; Muhammad Firdaus (Universitas Katolik Widya Karya Malang, 2023)
The research aims to determine the Ar-Risala Da'wah Communication Pattern in the Development of the Akit Tribe Converting Community in Sungai Upih Village, Kuala Kampar District, Pelalawan Regency. This research method uses a qualitative research approach, namely by conducting research that produces descriptive data, the research method is by conducting interactive direct observations and explaining according to the data obtained. The results of the research on Ar-Risala Da'wah Communication Patterns in the Development of the Akit Tribe Converted Community in Sungai Upih Village, Kuala Kampar District, Pelalawan Regency which the researchers made based on data that the researchers had obtained from observations, interviews and documentation during the research process. Based on the results of the research and discussion, it can be concluded that communication between the supervisors and the Akit tribe converts went well Keywords: Ar-Risala Da'wah Communication Pattern, Akit Tribe Converts